Comparative Analysis of the Performance of Gasoline and LPG-Powered Water Pumps in Shallow Wells - Rama Pien, Muh; Haerani; Munir, Ahmad (Program Studi Teknik Pertanian Universitas Hasanuddin, 2023)
One application of technology in agriculture is the use of water pumping machines to provide water for plants. Various innovations have been made to reduce the operating costs of water pumps, one example is to use Liquifield Petroleum Gas (LPG) to replace gasoline fuel. This study aims to compare the performance and efficiency of gasoline-fueled (BBM) and gas-fueled (BBG) pumps. This study uses several observation parameters including, calculating water discharge, analyzing gasoline and gas fuel requirements, calculating the power generated by the pump when raising water, and calculating engine torque. The results showed that the water discharge obtained for the fuel engine was 0.002808 m3 / second while for the gasoline engine it was 0.002961 m3 / second. The cost required for the operation of the BBM pump engine is Rp.23,615 / hour, while for BBG it is Rp.11,920 / hour. For the power generated by the BBM engine, it produces a power of 80.808 W, while for the BBG engine it produces a power of 83.882 W. The water pump engine in this study operates at a torque of 7.84 Nm. Based on the results of this study, it can be concluded that the use of LPG gas fuel in the rice field water pump engine is more efficient and the water discharge produced is also more than the fuel water pump.